2010
DOI: 10.1007/s00122-010-1311-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of a new Ty1-copia retrotransposon in durum wheat under salt and light stresses

Abstract: Long terminal repeat retrotransposons are the most abundant mobile elements in the plant genome and play an important role in the genome reorganization induced by environmental challenges. Their success depends on the ability of their promoters to respond to different signaling pathways that regulate plant adaptation to biotic and abiotic stresses. We have isolated a new Ty1-copia-like retrotransposon, named Ttd1a from the Triticum durum L. genome. To get insight into stress activation pathways in Ttd1a, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…RT-PCR analysis was performed using gene-specific primers for Asn1, Asn2 , and Asn3 isoforms (Wang et al, 2005; Gao et al, 2016), NR (Carillo et al, 2005; Wang et al, 2005), and degenerate primers for P5CS (Woodrow et al, 2016) (Table S1). The amount of TdAsn1, TdAsn2, TdAsn3, TdNR , and TdP5CS templates mRNA levels were based on the comparison with the level of the 190 bp mRNA for actin (Woodrow et al, 2010), a constitutively expressed “house-keeping” gene. The semi-quantitative PCR was used to estimate the transcript levels.…”
Section: Methodsmentioning
confidence: 99%
“…RT-PCR analysis was performed using gene-specific primers for Asn1, Asn2 , and Asn3 isoforms (Wang et al, 2005; Gao et al, 2016), NR (Carillo et al, 2005; Wang et al, 2005), and degenerate primers for P5CS (Woodrow et al, 2016) (Table S1). The amount of TdAsn1, TdAsn2, TdAsn3, TdNR , and TdP5CS templates mRNA levels were based on the comparison with the level of the 190 bp mRNA for actin (Woodrow et al, 2010), a constitutively expressed “house-keeping” gene. The semi-quantitative PCR was used to estimate the transcript levels.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic shocks, including biological or abiological stresses, and polyploidization can induce the mobilization of both class I and class II TEs (McClintock 1984; reference). Woodrow et al (2010) demonstrated that the retrotransposition of Ty1-copia-like elements plays important roles in defense responses to environmental stresses in tetraploid wheat. Allopolyploidy is a major driving force in plant evolution, inducing rapid structural changes in hybrid genomes; TEs are major components of those changes (Liu and Wendel 2000;Kashkush et al 2002;Josefesson et al 2006;Parisod and Senerchia 2012).…”
Section: Sequence-specific Amplified Polymorphism (Ssap)mentioning
confidence: 99%
“…Most of the comparisons had relatively higher q‐values; thus, only one (Retrotransposon protein, putative, Ty1‐copia subclass) was included in our further exploration (Table 2). Studying Ttdla , a Ty1‐copia‐like retrotransposon, Woodrow et al (2010) found that the activation and mobilization of the transposon was influenced by environmental stress as part of a defense mechanism. Therefore, the high number of differentially expressed RTs related to retrotransposons found in this study might be due to a water stress response.…”
Section: Discussionmentioning
confidence: 99%